2018
DOI: 10.1016/j.jbankfin.2017.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Sex and credit: Do gender interactions matter for credit market outcomes?

Abstract: This paper studies the effects of gender interactions on the supply of and demand for credit using data from a large Albanian lender. We document that first-time borrowers assigned to officers of the opposite sex are less likely to return for a second loan. The effect is larger when officers have little prior exposure to borrowers of the other gender and when they have more discretion to act on their gender beliefs, as proxied by financial market competition and branch size. We also find that first-time borrow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 39 publications
1
41
1
1
Order By: Relevance
“…Evidence emerging from gender literature suggests that involvement of women in management and executive designations, such as board members, leads to an improvement in organizational performance (Strøm, D'Espallier and Mersland 2014). Beck, Behr and Madestam (2018) and Bibi et al (2018) find that female officers have a positive impact on financial efficiency. Indicators for female employees and management in this study were found having no significant impact on efficiency contrary to Strøm, D'Espallier and Mersland (2014).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Evidence emerging from gender literature suggests that involvement of women in management and executive designations, such as board members, leads to an improvement in organizational performance (Strøm, D'Espallier and Mersland 2014). Beck, Behr and Madestam (2018) and Bibi et al (2018) find that female officers have a positive impact on financial efficiency. Indicators for female employees and management in this study were found having no significant impact on efficiency contrary to Strøm, D'Espallier and Mersland (2014).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Vectors and constitute a set of control variables relating to the cooperative (total assets, and urban or rural), and to the borrower (gender, length of membership, marital status, and business activity) and the loan (type, size, and issuing year), respectively. These variables, routinely used in the microfinance literature, are meant to reduce the omitted-variable bias as much as possible (Beck et al, 2018;Agier and Szafarz, 2013a and b) 6 . is the idiosyncratic error term.…”
Section: Context and Methodsmentioning
confidence: 99%
“…Some previous empirical evidence shows that women have behavioral and attitudinal differences compared to males (Beck et al 2018). Female CEOs/directors tend to be less overconfident in their decision making than men, and are more likely to express their independent views than male directors.…”
Section: Particularities Related To Post-communist Economiesmentioning
confidence: 97%